α-Tocopherol microencapsulation using chitosan and alginate: swelling behaviour under different pH - Ribeiro, Andreia (2012)
Vitamin E is known for its antioxidant activity, particularly for its effective protection against lipid oxidation. Currently, the intake of this important class of bioactive compounds is associated with health benefits. Moreover, due to its antioxidant capacity, vitamin E is frequently added to several foods in order to extend shelf life, mainly by inhibiting lipid oxidation. Vitamin E comprises a set of eight compounds (-, -, -, -tocopherols and tocotrienols), of which -tocopherol is considered, in vitro, to present the highest capacity of free radicals uptake. Due to -tocopherol instability and sensitivity towards temperature, oxygen and light, vitamin E supplements are generally administered in its most stable form (acetate or succinate derivatives). However, these forms are considered to have a lower intestinal absorption. In this perspective, microencapsulation can be a viable alternative to preserve -tocopherol thus maintaining its bioavailability in foods and other target products. In this study, microencapsulation of -tocopherol was tested using two polymeric matrices (chitosan and alginate). The obtained microspheres were submitted to acidic, neutral and basic media in order to evaluate its behaviour under pH conditions similar to those of the gastrointestinal tract (acid and basic for stomach and intestine, respectively) and under storage conditions (neutral).